Single nucleotide polymorphism rs3746444 in miR‑499a affects susceptibility to non‑small cell lung carcinoma by regulating the expression of CD200 - Ge, Nan; Mao, Chunxia; Yang, Qingbo; Han, Bin; Wang, Yongjie; Xu, Linhao; Yang, Xiuzhi; Jiao, Wenjie; Li, Chuan (International journal of molecular medicine, 2019)
The present study evaluated the association between single nucleotide polymorphism (SNP) rs3746444 and the risk of non‑small cell lung carcinoma (NSCLC) in a Chinese population. Computational analyses and luciferase assays were performed to investigate the regulatory relationship between miR‑499a and CD200. In addition, reverse transcription‑quantitative polymerase chain reaction and western blot assays were performed to examine the effect of rs3746444 on the expression of miR‑499a and CD200. The results demonstrated a significant difference in the smoking history of patients carrying malignant pulmonary nodules and those carrying benign pulmonary nodules. Furthermore, CD200 was demonstrated to be a direct target of miR‑499a, and a miR‑499a binding site was located in the 3'UTR of CD200. Notably, the levels of miR‑499a in malignant pulmonary nodules were higher compared with benign pulmonary nodules, while the levels of CD200 were higher in benign pulmonary nodules compared with malignant pulmonary nodules. In addition, the subjects carrying the AA genotype of SNP rs3746444 exhibited upregulated miR‑499a expression and reduced CD200 expression, compared with the subjects carrying AG and GG genotypes. These findings indicate that the SNP rs3746444 in miR‑499a could affect the prognosis of NSCLC patients by regulating the expression of CD200.